Steganography of Text Insertion into Image with End of File (EOF) Method - Sanbenfri Saragih; Eric Simanjuntak; Yebi Susani Rajagukguk; Diva Ferdinan Silalahi; Shevchenko Lumbanbatu (Jurnal Teknik Indonesia, 2023)
Steganography is a technique for hiding information in digital media with the aim of maintaining data confidentiality. This study discusses the End of File (EOF) method for inserting text into digital images without changing the image pixels. This method works by adding text data in binary form to the end of the image file, which allows re-extraction without visual distortion. In this study, an experiment was conducted by inserting the text "Hello" into an image file of 86.61 KB. The encryption process involves converting the text into 8-bit ASCII code, adding an EOF Marker (111111111111110), and storing the data into an image file. The calculation results show that text insertion increases the image size by 7 bytes, making the final image size 86.61 KB. This method has proven effective in inserting messages without changing the visual structure of the image. However, the file size increases with the length of the inserted message. This study provides insight into the use of the EOF method in steganography and its potential for application in digital data security.